KULTUR PESANTREN: RELASI KIAI, SANTRI, DAN KITAB KUNING - Nur Fatoni (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes the boarding school culture which focuseson the relation among Islamic scholar, students at Muslim school, andkitab kuning. The data colleting method which is used in this researchare observation, interview and documentation. This article shows thatthe soul of Islamic boarding school is the Islamic scholar and the supportingfactors are students and kitab kuning. This combination is inseparable.The Islamic scholar responds the modernity by teaching that holybooks in some levels based on the students’ ability.